SBAs, EMQs & SAQs in medicine - Hanks, Matthew (Tfm Publishing Ltd, 2019)
SBAs, EMQs & SAQs in MEDICINE provides a broad range and style of questions, not only for medical students preparing for their final exams, but also for clinicians preparing for their postgraduate exams.